2016
DOI: 10.1038/mp.2015.221
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment of antipsychotic-induced dyslipidemia: an analysis of two randomized, placebo-controlled trials

Abstract: Dyslipidemia is one of the most common adverse effects in schizophrenia patients treated with antipsychotics. However, there are no established effective treatments. In this study, data were pooled from two randomized, placebo-controlled trials, which were originally designed to examine the efficacy of metformin in treating antipsychotic-induced weight gain and other metabolic abnormalities. In total, 201 schizophrenia patients with dyslipidemia after being treated with an antipsychotic were assigned to take 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 37 publications
3
41
1
3
Order By: Relevance
“…Flow of the study selection process for a systematic review and meta-analysis 항정신병약물에 의한 체중증가에 미치는 메트포르민의 영향 / 207 37) 대해 비뚤림 위험을 평가하였다. '무작위 배정 순서 생성' 항 목에서 4개 연구가 24,26,30,37) '불확실'로, 그 외 연구들은 '낮음' 으로 평가되었다. '배정순서 은폐'의 경우도 4개 연구가 24,26,29,30) '불확실'로, 그 외 연구들은 '낮음'으로 평가되었다.…”
Section: 문헌의 질평가unclassified
See 2 more Smart Citations
“…Flow of the study selection process for a systematic review and meta-analysis 항정신병약물에 의한 체중증가에 미치는 메트포르민의 영향 / 207 37) 대해 비뚤림 위험을 평가하였다. '무작위 배정 순서 생성' 항 목에서 4개 연구가 24,26,30,37) '불확실'로, 그 외 연구들은 '낮음' 으로 평가되었다. '배정순서 은폐'의 경우도 4개 연구가 24,26,29,30) '불확실'로, 그 외 연구들은 '낮음'으로 평가되었다.…”
Section: 문헌의 질평가unclassified
“…3). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 또한, 연구 시작 점에 과체중이었던 연구대상자만을 분석했을 때에도 placebo 군에 비해 metformin 군에서 유사한 정도의 체질량지수 감소 가 관찰되었다(WMD: -0.91; 95% CI: -1.11, -0.71; p<0.00001; I 2 : 28%). 24,25,28,[31][32][33][34][35][36] 더하여, 소아를 대상으로 한 연구를 24,26) 배제한 후 연구시작점에서의 체질량지수에 무관하게 성인환 자만으로 분석했을 때, 체중의 경우 소아를 포함했을 때와 거의 차이가 없었다(체중, WMD: -2.17; 95% CI: -2.72, -1.63; p<0.00001; I 2 : 29%; 체질량지수, WMD: -0.89; 95% CI: -1.06, -0.71; p<0.00001; I 2 : 42%) ( Supplementary Fig.…”
Section: 문헌의 질평가unclassified
See 1 more Smart Citation
“…In the past two decades, weight gain induced by APs has attracted increased attention [11][12][13][14][15][16]. Weight gain is associated with poor treatment adherence and quality of life, higher rate of medical comorbidity particularly cardiovascular diseases, diabetes mellitus, and osteoarthritis and mortality [12,13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that nutritional counselling (n = 95) was significantly superior to treatment as usual (n = 75) in attenuating AP-related weight gain [16]. In addition, several RCTs [3,[17][18][19] and meta-analyses [2,[20][21][22] have found that metformin is effective, safe, and well tolerated in reducing AP-related weight gain in schizophrenia patients.…”
Section: Review Registration: Crd42017059198 Introductionmentioning
confidence: 99%